Development of high‐resolution 3D MR fingerprinting for detection and characterization of epileptic lesions. Issue 5 (23rd December 2018) - Ma, Dan; Jones, Stephen E.; Deshmane, Anagha; Sakaie, Ken; Pierre, Eric Y.; Larvie, Mykol; McGivney, Debra; Blümcke, Ingmar; Krishnan, Balu; Lowe, Mark; Gulani, Vikas; Najm, Imad; et al.
Abstract : Background: Conventional MRI can be limited in detecting subtle epileptic lesions or identifying active/epileptic lesions among widespread, multifocal lesions. Purpose: We developed a high‐resolution 3D MR fingerprinting (MRF) protocol to simultaneously provide quantitative T1, T2, proton density, and tissue fraction maps for detection and characterization of epileptic lesions. Study type: Prospective. Population: National Institute of Standards and Technology (NIST) / International Society for Magnetic Resonance in Medicine (ISMRM) phantom, five healthy volunteers and 15 patients with medically intractable epilepsy undergoing presurgical evaluation with noninvasive or invasive electroclinical data. Field Strength/Sequence: 3D MRF scans and routine clinical epilepsy MR protocols were acquired at 3 T. Assessment: The accuracy of the T1 and T2 values were first evaluated using the NIST/ISMRM phantom. The repeatability was then estimated with both phantom and volunteers based on the coefficient of variance (CV). For epilepsy patients, all the maps were qualitatively reviewed for lesion detection by three independent reviewers (S.E.J., M.L., I.N.) blinded to clinical data. Region of interest (ROI) analysis was performed on T1 and T2 maps to quantify the multiparametric signal differences between lesion and normal tissues. Findings from qualitative review and quantitative ROI analysis were compared with patients' electroclinical data to assess concordance. Statistical Tests: Phantom results were compared using R‐squared, and patient results were compared using linear regression models. Results: The phantom study showed high accuracy with the standard values, with an R 2 of 0.99. The volunteer study showed high repeatability, with an average CV of 4.3% for T1 and T2 in various tissue regions. For the 15 patients, MRF showed additional findings in four patients, with the remaining 11 patients showing findings consistent with conventional MRI. The additional MRF findings were highly concordant with patients' electroclinical presentation. Data Conclusion: The 3D MRF protocol showed potential to identify otherwise inconspicuous epileptogenic lesions from the patients with negative conventional MRI diagnosis, as well as to correlate with different levels of epileptogenicity when widespread lesions were present. Level of Evidence: 3. Technical Efficacy Stage: 3. J. Magn. Reson. Imaging 2019;49:1333–1346.